2010
DOI: 10.5114/aoms.2010.13509
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of prognostic significance of proliferating cell nuclear antigen expression in advanced primary larynx carcinomas and lymph node metastases

Abstract: IntroductionThe aim of this study was to investigate the prognostic significance of proliferating cell nuclear antigen (PCNA) expression in laryngeal carcinoma in relation to clinicopathological features. Special emphasis was placed on examining the relationship of PCNA expression in the primary tumour and PCNA expression in corresponding lymph node metastases obtained from the same patients.Material and methodsThe study included 60 patients with advanced larynx carcinoma who had received treatment and follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, ROC analysis showed that the use of serum PGE-2 concentration as a biomarker in ESCC is doubtful. The diagnostic parameters for PGE-2 were significantly lower than for other tested factors [26, 32, 33]. The best diagnostic potential for ESCC was found for C-reactive protein [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, ROC analysis showed that the use of serum PGE-2 concentration as a biomarker in ESCC is doubtful. The diagnostic parameters for PGE-2 were significantly lower than for other tested factors [26, 32, 33]. The best diagnostic potential for ESCC was found for C-reactive protein [28].…”
Section: Discussionmentioning
confidence: 99%
“…Larynx cancer is strongly associated with smoking and high alcohol consumption, as well as occupational and environmental exposure to carcinogens [1–3]. Cigarette smoke can generate reactive oxygen species, which are capable of inducing DNA double-strand breaks (DSBs) [4], the most serious DNA damage, which, if not repaired or misrepaired, may result in genomic instability, cancer transformation or cell death [57].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of some of these proteins reported in head and neck cancer in previous studies was consistent with our findings. For example, PCNA, CDK2, and p27 were upregulated in laryngeal carcinoma, [7][8][9] and Bcl-xL, MMP9, HMG-1, and p38 were upregulated in head and neck cancer. [10][11][12][13] However, the expression of some of the proteins differed from that described in previous publications.…”
Section: Discussionmentioning
confidence: 99%